A sacralidade do templo como instrumento de evangelização: uma retrospectiva bíblica e histórica até às primeiras vilas do Ceará (séculos XVII e XVIII). - Morais, José Maria Bonfim de (2020)
The present work aims to present studies on the sacredness of the temple, a religious space par excellence, which arose in the ancient world and which had a privileged place in the culture of the people of Israel. In Christianity, throughout history and in the early days of the colonization of Brazilian lands, temples were used as an instrument of evangelization, according to the mentality of the time. The arrival of religious missionaries to Brazil had the apostolic motivation of converting the “foresters”. Evangelization observed the canons dictated and followed by the Roman Catholic Apostolic Church. Bringing the Christian message to these peoples was the main objective of the evangelization that was carried out by missionaries from various religious entities. Based on bibliographic research in renowned authors such as Mircea Eliade, Rufolf Otto and Émile Durkheim, and the concepts they elaborate that deal with the importance of sacred places for humanity, for Religions and for Christianity, this study is divided into three chapters. In the first, we try to understand the different hierophanies (manifestations of the divine) in physical spaces that, little by little, become sacred spaces. In this way, the temple is conceived as a consecrated place to experience these manifestations of God; it is the environment in which contact with the Transcendent is sought, through people, objects and natural elements that mediate this contact. In the second chapter, it is investigated how the sacred spaces were important for the people of Israel, above all, from the mysticism generated around the Temple of Jerusalem. Authors like Margaret Barker have developed studies on the theological conception of Temple, present in the Old Testament, which had a strong impact on the theological conception of the Risen Jesus, the new Temple. Jesus' death opened the doors of the Temple wide open for everyone to take a seat in it. In the last chapter, it is shown that Catholic temples were taken as a starting point for the evangelization of the first Jesuit missions in Latin America and Brazil. Around these sacred spaces appeared the first villages in the Northeast and in the State of Ceará. Undoubtedly, over millennia, the temple has been and remains the foundation and pillars where people meet under the same roof, to experience God. The Temple is a sacred space not only to find God, but also to find God in each other.